A causal relationship of occupational stress among university employees - Kaewanuchit, C. (Iranian Journal of Public Health, 2015)
Background: Occupational stress is a psychosocial dimension of occupational health concept on social determinants of health, especially, job & environmental condition. Recently, staff network of different government universities of Thailand have called higher education commission, and Ministry of Education, Thailand to resolve the issue of government education policy (e.g. wage inequity, poor welfare, law, and job & environment condition) that leads to their job insecurity, physical and mental health problems from occupational stress. The aim of this study was to investigate a causal relationship of occupational stress among the academic university employees. Methods: This cross sectional research was conducted in 2014 among 2,000 academic university employees at Thai government universities using stratified random sampling. Independent variables were wage, family support, periods of duty, and job & environmental condition. Dependent variable was stress. Results: Job & environmental condition, as social and environmental factor, and periods of duty as individual factor had direct effect to stress (P< 0.05). Family support, as family factor, and wage, as individual factor had direct effect to stress (P < 0.05). Both family support and wage were the causal endogenous variables. Conclusion: Job & environmental condition and periods of duty were increased so that it associated with occupational stress among academic university employees at moderate level. Â© 2015 Iranian Journal of Public Health. All Rights Reserved.